Les bouleversements de l’espace-temps - Céline Bryon-Portet (Communication)
Information and communication technologies modify the human perception of reality, and more specifically the notions of space and time. In turn this impact of technology alters the relationship that individuals hold with traditions of commemoration and with the sites where such commemorations take place. The author argues that the Internet, by operating a displacement of the human memory towards the computer memory, and by introducing a feeling of dematerialization and synchrony, triggers a compensatory reaction that manifests itself in the multiplication of commemorative ceremonies and places dedicated to events of the past.